Pelatihan Platting Art Siswa Smk Tata Boga & Perhotelan Jawa Tengah - Ahmad Mansur; Bayu Ade Prabowo; Khairil Anwar (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The aftermath of Covid-19 significantly impacted the culinary industry in Indonesia, leading to a decline in culinary and hospitality education. In response, STIEPARI Semarang collaborated with the Indonesian Chef Association (ICA) BPD Central Java to address the reduced interest in this field. The community service aimed to enhance the plating skills of high school and university students, focusing on traditional dishes. The program involved 10 students from vocational schools and university students majoring in hospitality in Semarang. Training sessions, led by ICA experts, concentrated on plating traditional foods like onde-onde, lumpia, gethuk, corobikan, kue ku, and others. Faculty members from UDINUS and STIEPARI, along with ICA Central Java members, actively participated. The initiative not only improved practical skills but also aimed to increase the market value of traditional dishes through appealing presentations. Results showed improved plating skills, especially with traditional dishes, contributing to higher sales potential. Furthermore, the initiative positively impacted the preservation of culinary heritage. Thus, this community service not only enhanced students' skills but also promoted and preserved traditional culinary practices, positively impacting education, tourism, and the culinary industry in Central Java.